Fulfillment of Wife's Nafkah Rights: Identification of Constraints and Implications for Household Harmony - Habibie, Imsaskia Zalzabilha (Damhil Law Journal, 2024)
The fulfillment of a wife's right to maintenance is a fundamental obligation in the marital relationship that relates to the physical and emotional well-being of the couple. Economic factors play a huge role in this fulfillment, as the inability of husbands to provide sufficient maintenance is often a source of tension in the household. This study aims to identify the impact of economic factors on household harmony, especially in the context of wife's fulfillment of maintenance. Based on qualitative analysis, this study found that a husband's inability to fulfill his maintenance obligations can lead to feelings of pressure, anxiety and inferiority in the husband, as well as dissatisfaction and a sense of abandonment in the wife. In addition, financial strain often worsens communication between spouses and leads to conflict in their relationship. The study also shows that while many wives contribute economically, these contributions are often not recognized in the fulfillment of maintenance. Therefore, this study suggests the importance of open communication and mutual respect between husbands and wives, as well as the role of family and community support to overcome economic problems. In addition, women's economic empowerment and government programs to help families in economic difficulties are also important steps to create harmony in the household. This research provides new insights into the relationship between economic factors and household harmony, and offers solutions that can be applied to improve the quality of family life.